Strengthening National Immunization Technical Advisory Groups in resource-limited settings: current and potential linkages with polio national certification committees - Sharon A. Greene; Blanche-Philomene Melanga Anya; Humayun Asghar; Irtaza A. Chaudhri; S. Deblina Datta; Morgane E. Donadel; Koffi Isidore Kouadio; Abigail M. Shefer; Kathleen F. Cavallaro (BMC, 2020)
Abstract Background Countries are transitioning assets and functions from polio eradication to integrated immunization and surveillance activities. We assessed the extent of linkages between and perceptions of National Immunization Technical Advisory Groups (NITAGs) and National Certification Committees (NCCs) for polio eradication to understand how linkages can be leveraged to improve efficiencies of these expert bodies. Methods During May 2017 to May 2018, we administered a 15-question survey to a NITAG chair or member and an NCC counterpart in all countries of the WHO Regions for Africa (AFR) and for the Eastern Mediterranean (EMR) that had both a NITAG and an NCC. Data were analysed using frequency distributions. Results Of countries with both a NITAG and an NCC (n = 44), the response rate was 92% (22/24) in AFR and 75% (15/20) in EMR. Some respondents reported being very familiar with the functions of the other technical bodies, 36% (8/22) for NITAG members and 38% (14/37) for NCC members. Over 85% (51/59) of respondents felt it was somewhat useful or very useful to strengthen ties between bodies. Nearly all respondents (98%, 58/59) felt that NCC expertise could inform measles and rubella elimination programmes. Conclusions We observed a broad consensus that human resource assets of NCCs may serve an important technical role to support national immunization policy-making. At this stage of the polio eradication initiative, countries should consider how to integrate the technical expertise of NCC members to reinforce NITAGs and maintain the polio essential functions, beginning in countries that have been polio-free for several years.